Multidisciplinary treatment of total vertical excess and transverse maxillary deficiency without posterior crossbite - Michele García Menéndez; Yusleni Hernández Galvez; Jeydel Abull Juaregui; Pedro Antonio Ducasse Olivera; Olga Ileana Ruiz Galvez (Editorial Ciencias Médicas, 2022)
Introduction: The correction of the vertical excess of the maxilla will bring not only vertical changes in the profile, but also sagittal and transverse ones. The clinical absence of posterior crossbite can mask width deficiencies and lead to incorrect treatment plans. Objective: Describe the most important aspects in the care of a case with vertical excess and transverse deficiency of the maxilla without posterior cross bite. Case presentation: A 26-year-old female patient comes to the consultation for "teeth forward". The physical examination and the study of the diagnostic means allowed to conclude the existence of vertical excess and transverse deficiency of the maxilla. Clinically, no posterior crossbite was observed. Staged treatment included orthodontics, expansion and surgical impaction of the maxilla. Conclusions: The surgical ascent of the maxilla should be planned based on a holistic analysis. It includes the sagittal changes of the profile and the transverse relationship between the arcades, caused by the effect of mandibular rotation. The absence of posterior crossbite does not exclude the existence of transverse maxillary deficiency. Likewise, the definitive dimension of the expansion must be established once the lower arcade reaches its definitive dimensions.